Effects of Dietary Energy Levels on Rumen Fermentation, Gastrointestinal Tract Histology, and Bacterial Community Diversity in Fattening Male Hu Lambs - Wang, Qiye; Zeng, Yutong; Zeng, Xianglin; Wang, Xin; Wang, Yancan; Dai, Chunpeng; Li, Jianzhong; Huang, Pengfei; Huang, Jing; Hussain, Tarique; Zhu, Mingzhi; Yang, Huansheng (Frontiers in Microbiology, 2021)
This study investigated rumen fermentation, histological and microbial diversity in male Hu lamb fed diets with different metabolizable energy (ME) levels (MEA, 9.17 MJ/kg, MEB, 10.00 MJ/kg, and MEC, 10.82 MJ/kg). Thirty-six male Hu lambs were randomly allotted to three treatments and the feeding trial lasted for 67days. Rumen fermentation results suggest that the iso-valerate had a significant effect by dietary energy level. The papillary height (PH) of rumen was the highest in MEB group, the crypt depth (CD) was significantly increased in duodenum and jejunum, and the villus height (VH) to CD ratio (VH/CD) was significantly decreased in duodenum by increasing dietary energy levels, the VH, villus width (VW) and VH/CD were also significant differences in ileum. 16S rRNA sequencing results showed that the OTUs number, the ACE and Chao1 indices were linearly decreased by increasing dietary energy level; 24 phyla including 124 genera were identified, the relative abundance of Papillibacter and Quinella linearly decreased by increasing the dietary energy level. Compared to MEA and MEB groups, whereas the relative abundance of unidentified_Veillonellaceae and Anaerovibrio was significantly increased in MEC group at the genus level. The relative abundance of carbohydrate metabolism pathway predicted by PICRUSt was linearly increased by increasing the dietary energy levels. Three metabolic pathways were identified in the KEGG level 3 were significantly influenced as the dietary energy level increased. In summary, these results demonstrated that the dietary energy levels affected the rumen fermentation parameters, morphological structures of the gastrointestinal tract (GIT) and the composition and function of rumen microflora in male Hu sheep.